Silencing of G0/G1 switch gene 2 in cutaneous squamous cell carcinoma - Nobeyama, Yoshimasa (PLoS One, 2017)
BACKGROUND: Methylation of a CpG island (CGI; a dense cluster of CpGs) located in the 5' region of a gene suppresses that gene's transcription. The expression of G0/G1 switch gene 2 (G0S2) is potentially associated with tumorigenesis. The aim of this study is to elucidate the methylation status of the CGI located in the 5' region of G0S2 (hereinafter called 5' G0S2 CGI) in cutaneous squamous cell carcinoma (SCC). METHODS: Quantitative real-time methylation-specific PCR (RT-MSP) and bisulfite sequencing were performed to evaluate the methylation statuses of cutaneous SCC and normal epithelial cell samples. Quantitative real-time reverse transcription-PCR was performed to evaluate RNA expression levels. Immunohistochemical analysis was performed to detect protein expression. RESULTS: G0S2 was suppressed in the five SCC cell lines with 5' G0S2 CGI methylation levels of nearly 100.0% and was expressed in the two normal cultured keratinocytes with methylation levels of almost 0.0%. G0S2 was re-expressed in SCC cell lines treated with a demethylating agent. The in vivo methylation levels of 5' G0S2 CGI as determined by RT-MSP varied widely (0.0% to 77.7%) in 17 cutaneous SCC samples and narrowly (0.1% to 7.3%) in 6 normal epidermis samples. Nine cutaneous SCC samples exhibited higher methylation levels than the highest methylation level (7.3%) of the 6 normal epidermis samples. Bisulfite sequencing showed dense methylated CpG sites within 5' G0S2 CGI in these highly methylated cutaneous SCC samples. The methylation levels of the cutaneous SCC samples did not correlate with any clinical parameters investigated or with histopathological grading. CONCLUSIONS: G0S2 is silenced by aberrant DNA methylation in a subset of cutaneous SCCs.